Clinical Pattern of Pediatric Dermatoses Attending a Multi-Specialty Hospital - Jha, Harendra Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Pediatric dermatoses deal with skin disease in children from birth to 18 years. This age group comprises significant physiological changes, and hence the pattern of disease including skin disease is unique to them. Skin diseases are influenced by the local climatic factor and socio-economic status which differ in different geographic areas including within the country.Objective: The objective of the study was to analyze the clinical spectrum of skin disease in children from 1 day to 18 years of age and to find any seasonal influence on the disease pattern.Methodology: The study was conducted retrospectively in a multi- specialty hospital from May 2014 to April 2015. Data of children from 1 day to 18 years of age were analyzed. Demographic details like age, sex, ethnicity was noted. The month and season of the presentation were also recorded. Patient with a confirmed clinical diagnosis and adequate data was included in the study. Patients were divided into 5 age groups; neonate (0 days to 1 month), infant (1 month to 2 years), young child (2-6 years), child (6-12 years), and adolescent (12-18 years). Data were entered in Microsoft excel and analysis was done with SPSS version 22 along with the Chi-square test.Result: There were 20.65% of pediatric patients out of 3292 patients visiting skin OPD. The male to female ratio was 1.63:1. The majority of the cases (47.8%) were in the adolescent age group. Infection and infestation were the predominant diagnosis (56.02%), followed by eczema (15.88%) and urticaria (6.47%). Among infection, fungal infection was seen as the majority (26.17%).Papular urticaria and urticaria were significantly (p-value